Development of Transformational Leadership Instrument to Measure Principal's Leadership - Iyan Irdiyansyah; Nita Karmila; Citra Agustina; Khansa Rohadatul Aisy (Journal of Innovation in Educational and Cultural Research, 2024)
The transformational leadership instrument has been used to analyze academic leadership behavior and to gather data on academics' perceptions of transformational leadership. The instrument development used RnD and Confirmatory Factor Analysis (CFA) to confirm, analyze, and develop the items. The instrument design followed a four-step process (4-D model) to construct 39 items on a Likert scale. The instrument items were reviewed and revised based on expert judgment. A panel tested and analyzed the revised items using Aiken's V Index to assess their validity. As much as 82% of the items were found to have good validity criteria. The reliability test results were highly significant. The final instrument was confirmed to have a good fit model and can be used as a standardized tool by educational institutions. A multi-step process to develop and validate a transformational leadership instrument involves expert review, statistical analysis, and confirmation of the instrument's psychometric properties. The high validity and reliability of the final instrument make it a potentially useful tool for assessing transformational leadership in educational settings. The detailed description of the development process provides confidence in the quality of the instrument.